The effect of Tualang honey versus Honey Cocktail (HC 124) on safety, physiological and psychosexual changes among postmenopausal women - Hussain, Nik Hazlina Nik (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2017)
Introduction: Beehive products such as royal jelly and bee bread have been reported to contain higher minerals. vitamins, free fatty acid and amino acids compared to honey alone. Hence. a combination of beehive products known as Honey Cocktail may provide additional values to Tualang Honey. Objective: To investigate the effects of Tualang Honey (TH) versus Honey Cocktail (HC) (a mixture of honey. bee bread and royal jelly) on safety, physiological (cardiovascular. anthropometric measurements, hormonal profile and bone densitometry) and psychosexual changes (psychosexual and quality of life) among postmenopausal women. Methods: A randomized. double blinded two-armed parallel study involving 100 postmenopausal women aged 45 to 65 was conducted in the ratio of 1 : 1 into either 20 g/day of TH or HC for twelve months duration. Safety profile [(Renal Function Test (RFT) and Liver .Function Test (LFT)J, cardiovascular parameters [(systolic blood pressure (SBP), diastolic blood pressure (DBP), total cholesterol (TC), triglycerides (TG), high density lipoprotein (HDL), low density lipoprotein (LDL) and fasting blood sugar (FBS). anthropometric measurements [body mass index (BMI), waist circumference (WC), body fat percentage (Fat%)]. hormonal profile [follicle stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2) and testosterone(T)], bone densitometry (T-score), psychosexual changes (self administered FSFI and WHO) were assessed at baseline, six months and 12 months. RM A NOVA and ANCOVA were performed with SPSS version 22.0 was used for data analysis. Duration of menopause was controlled as covariate for hormonal analysis. Meanwhile, for T-score analysis, duration of menopause and E2 level were controlled. Results: There were no significant differences between the groups in serum creatinine, alanine amino transferase and aspartate aminotransferase level at baseline. 6 months and 12 months. However, there were significant improvements in the BMI (p<0.001), WC (p<0.001), Fat% (p<0.001), E2 levels (p=0.043) and T-score (p=0.047) in HC group compared to TH group at 12 months. There were significant improvements in DBP (p=0.014), FBS (p=0.017) and FSH (p=0.006); in TH group compared to HC group at 1 2 months. Other parameters were not significantly different. There was a significant improvement in the overall FSFI scores(p=0.016) in the HC group compared to the TH group at 12 months.